Goal-Directed Approach and Design Principle Approach: a Comparative Study - Meei Hao, Hoo; Jaafar, Azizah; Hooi Ching, Beh (International Journal of Engineering and Technology, 2018)
Uncertainty arises from intuitive design, prioritize usability goal, trade-off among usability attributes, choose usability patterns, conflict opinion during evaluation are putting more difficulties for novice designers in design tasks. As previous studies focused on the effectiveness of novice designers through the use of design patterns, we extended the use of usability pattern to look into the delivery of prototype design. Furthermore, in the aspect of usability analysis, Analytical Hierarchical Process (AHP) technique was applied in the prioritization of usability criteria and usability problems. In this study, AHP is used to prioritize the usability goals and integrated with usability testing and cognitive walkthrough to affirm the result for better judgement. We developed the approach to guide novice designers for the achievement of the targeted usability goal and supported with a tool to capture the collective decisions in providing convinced result during comparative evaluation. We built the approach and compared it using an experimental study with the undergraduate students. Our results suggested that prototype designed by novice designers followed usability pattern approach would has more usability patterns applied into and was preferred by experts than using design principle approach.Â Â